Developing Restriction Associated DNA Tags for the Ion Torrent Personal Genome Machine - Agyabeng-Dadzie, Fiifi (My University, 2014)
The identification and classification of similar cryptic species such as Kryptolebias marmoratusand Kryptolebias ocellatus,as distinct species has always been problematic within the biological sciences. Though Kryptolebias marmoratusand Kryptolebias ocellatusare both known to be self-fertilizing hermaphrodites, out crossing has been observed resulting in heterozygous offspring. Recently, a viable hybrid (Gitmo) between K. marmoratusand K. ocellatushas been isolated in the Valdosta State University aquatic lab. This hybrid questions the proposed species status of these fishes. Classifications of organisms are usually based on both morphological and genotypic studies. Based on morphological studies, both fishes were thought to be synonymous because of very similar anatomical and physiological characteristics. Mitochondrial studies (genotypic analysis) ofthese fishes have suggested otherwise. Unfortunately, thorough whole genome studies are very expensive and labour intensive. Methods such as Restriction Fragment Length Polymorphisms (RFLP), Amplified Fragment Length Polymorphisms (AFLP) and microsatellite analysis are more commonly used. These methods, though helpful, make analyses based on the length polymorphisms of the DNA fragments and only a small portion of the genome. Furthermore, surveys yield a very limited amount of genetic information. A more reliable method of analyzing large numbers of these genotypic markers concurrently would be extremely valuable for taxonomic questions. Developing Restriction Associated DNA Tag (RADTag) genome sequencing using methods for the Ion Torrent Personal Genome Machine (PGM) provides a way not only to cut down the cost of genomic sequencing but also provides a method that performs thousands of Single Nucleotide Polymorphisms (SNP) analyses atonce, without the use of a reference sequence. Analysis of RADTag sequences on public domains “Stacks” software displayed thousands of markers present in the Hon9 (Kryptolebias marmoratus) genome and confirms the Hon9 strain to be highly homozygous (0.999) across all loci. This achievement paves the way for further genomic studies with high throughputs and accuracy. This RADtag genome will provide the information needed for resolving the questionable relationship between K. marmoratusand the presumptive K. ocellatus cryptic species.
I INTRODUCTION 1 Cryptic Species 1 Genotypic Classification 2 II MATERIALS AND METHODS 5 Location 5 Ethics Statement 5 Mitochondria and Nuclei Separation 5 DNA Extraction 6 Library Preparation 7 Template Preparation 14 Sequencing 15 Analysis 15 III RESULTS 17 Genomic DNA Extraction 17 Digestion 17 Fragmentation 17 Ligation 18 Amplification 18 Emulsion Amplification 18 Sequencing 19 Analysis 19 IV DISCUSSION 21 Separation of Mitochondrial and the Nuclear Genomic DNA 21 Library 22 Emulsion PCR 24 Analyses of Sequences 25 Heterozygosity 25 Conclusion 27 BIBLIOGRAPHY 28 APPENDIX A: Figure 1 through 11 31 APPENDIX B: Tables 1 through 7 43 APPENDIX C: Examples of SNPs in Individual Samples 51 APPENDIX D: Valdosta State University Institutional Animal Care and Use Committee (IACUC) Approval 55
Keywords: Kryptolebias marmoratus; Biology; Kryptolebias ocellatus; Ion Torrent Personal Genome Machine; Restriction Associated DNA Tag; Restriction Fragment Length Polymorphisms; morphological studies; Valdosta State University aquatic lab; genotypic analysis; RAD-Tags; SNP analysis; AFLP; RFLP; cryptic species